Supporting Start-ups in Indonesia: Examining Government Policies, Incubator Business, and Sustainable Structure for Entrepreneurial Ecosystems and Capital - Bernardus, Denny; Arisa, Ma'rifani Fitri; Sufa, Siska Armawati; Suparwata, Dewa Oka (International Journal of Business, Law, and Education, 2024)
This research investigates the complex dynamics that shape the sustainability of start-ups in Indonesia, focusing on the influence of government policies, networks, capital structure, entrepreneurial ecosystem, and business incubators. Using Structural Equation Modeling with Partial Least Squares, this study analyzes data collected from 315 sample start-ups across various sectors. The results show significant relationships among the factors studied. Government policy emerges as a critical determinant, impacting business incubators and the broader entrepreneurial ecosystem. Networks and capital structures also play an essential role, in influencing business incubators and the entrepreneurial landscape. This study highlights the interconnectedness of these elements and underscores the importance of a holistic approach to foster sustainable start-ups. Theoretical implications suggest integrating factors in entrepreneurship models, emphasizing the role of policy-driven ecosystem development, network-centric approaches, and consideration of financial dynamics. Practical implications guide policy makers, entrepreneurs, investors, and business incubator managers in shaping a supportive and dynamic start-up ecosystem. While acknowledging limitations, this study contributes valuable insights into entrepreneurship and offers a foundation for future investigations into the sustainability of start-ups in various contexts.